The Biomarkers Procalcitonin and S100β Ptotein in the Clinical and Laboratory Monitoring of Neonatal Critical Conditions - I. B. Dmitriyeva; N. V. Beloborodova; E. A. Chernevskaya (Общая реаниматология)
Objective: to determine quantitative changes in procalcitonin (PCT) and S100β protein in serum from newborn infants under the long-term intensive care in an intensive care unit in order to optimize managing the care. Subjects and methods. A study group prospectively included 69 critically ill neonates of more than 2 days of birth admitted to the neonatal intensive care unit. The levels of PCT (normal values Results. In critically ill neonates, both biomarkers were shown to be increased in most cases. The level of PCT varied from the normal values up to 72 ng/ml [mean 1.03 (range 0.36—3.92 ng)]. Mean level of S100β protein was 0.339 (range 0.234—0.481) ^g/l. Levels of PCT and S100β positively correlated (r=0.47; p<0.05). The infants with the increased baseline levels of PCT demonstrated significant reduction of the biomarker over time that was considered as the adequacy of performed antibiotic therapy. The highest S100β levels were recorded in premature babies with sepsis including those without significant perinatal lesion of the central nervous system (CNS). Unidirectional reduction was typical for both S100β and PCT levels. Combination of increased S100β serum concentration decreased PCT was a pattern of developing the periventricular leukomalacia. There was evidence for a direct relation of biomarker S100β? to the presence of convulsive syndrome (Kendal’s coefficient 0.36; p<0.05). Conclusion. Similarly to newborn infants with traumatic, hypoxic, and hemorrhagic CNS lesions, patients with infectious and septic pathology exhibited elevated S100β levels. Both biomarkers PCT and S100β are suggested to be included in a battery of clinical and monitoring tests to optimize treatment of high-risk neonates in the intensive care unit. Key words: newborn infants, premature infants, critical conditions, biomarkers, procalcitonin, S100β protein, laboratory monitoring, perinatal pathology, antibacterial therapy.